PERCEPÇÕES SOBRE APRENDIZAGEM E USO DE LÍNGUA PORTUGUESA POR INDÍGENAS VENEZUELANAS DA ETNIA WARAO REFUGIADAS EM PACARAIMA/RR - Ísis Pereira dos Santos (Nepan editor, 2019)
This article aims to analyze the need for use and learning of the Portuguese language by indigenous Venezuelan refugee women of Warao ethnicity. A field research was conducted with a group of twenty women artisans from the Janokoida indigenous shelter, located in Pacaraima / RR, a municipality bordering Venezuela. The problema-tization was raised in the multilingual environment of migratory and border context from the perceptions about the need for learning and the use of the Portuguese language. The study used action research through Portuguese language workshops offered to artisans. The participatory observation technique was important for analyzing the context of language practices and the functioning of the shelter. After a qualitative analysis, the results indicated different perceptions regarding the interest in learning Portuguese, such as the use of the language for commercial necessity or the non-use for the protection of its identity references and the intention of short stay in Brazilian territory.